2022
DOI: 10.3847/1538-4357/ac63aa
|View full text |Cite
|
Sign up to set email alerts
|

A Radio, Optical, UV, and X-Ray View of the Enigmatic Changing-look Active Galactic Nucleus 1ES 1927+654 from Its Pre- to Postflare States

Abstract: The nearby Type II active galactic nucleus (AGN) 1ES 1927+654 went through a violent changing-look (CL) event beginning 2017 December during which the optical and UV fluxes increased by four magnitudes over a few months, and broad emission lines newly appeared in the optical/UV. By 2018 July, the X-ray coronal emission had completely vanished, only to reappear a few months later. In this work we report the evolution of the radio, optical, UV and X-rays from the preflare state through mid-2021 with new and arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 77 publications
3
35
2
Order By: Relevance
“…Others have suggested that possibly a magnetic flux inversion occurred in the accretion disk of 1ES 1927+654, whereby an advection event allowed magnetic flux with opposite polarity to propagate inward in the disk (Scepi et al 2021). The arguments supporting this idea include a delayed X-ray dip relative to the UV peak, a corresponding dip in the radio, and the return to the pre-outburst state following this event (Scepi et al 2021;Laha et al 2022). This model is thus in line with the interpretation put forth in this work if the anomalous flux inversion event creates a geometrically thick inner accretion flow.…”
Section: Clagn and Tdesmentioning
confidence: 99%
“…Others have suggested that possibly a magnetic flux inversion occurred in the accretion disk of 1ES 1927+654, whereby an advection event allowed magnetic flux with opposite polarity to propagate inward in the disk (Scepi et al 2021). The arguments supporting this idea include a delayed X-ray dip relative to the UV peak, a corresponding dip in the radio, and the return to the pre-outburst state following this event (Scepi et al 2021;Laha et al 2022). This model is thus in line with the interpretation put forth in this work if the anomalous flux inversion event creates a geometrically thick inner accretion flow.…”
Section: Clagn and Tdesmentioning
confidence: 99%
“…To date, a few dozen Seyfert galaxies and quasars have been known to have changed their optical spectral type, for example NGC 3516 (Collin-Souffrin et al 1973, Mehdipour et al 2022, NGC 7603 (Tohline & Osterbrock 1976;Kollatschny et al 2000), NGC 4151 (Penston & Perez 1984), Fairall 9 (Kollatschny & Fricke 1985, NGC 7582 (Aretxaga et al 1999), NGC 2617 (Shappee et al 2014), Mrk 590 (Denney et al 2014), HE 1136-2304(Parker et al 2016Zetzl et al 2018;Kollatschny et al 2018), Mrk 1018(McElroy et al 2016Husemann et al 2016;Kim et al 2018;Lyu et al 2021), 1ES 1927+654 (Trakhtenbrot et al 2019, Ricci et al 2020, Laha et al 2022, NGC 1566 (Oknyansky et al 2019;Parker et al 2019), and references therein. Further recent findings are based on spectral variations detected in large-scale surveys, such as the Sloan Digital Sky Survey (SDSS; e.g., Komossa et al 2008;LaMassa et al 2015;Rumbaugh et al 2018;MacLeod et al 2019), the Catalina Realtime Transient Survey (Graham et al 2020), or the Wide-field Infrared Survey Explorer (Stern et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These results clearly show that the disk/corona interaction in Mrk 590 does not follow the typical disk-corona properties of Seyfert 1 AGNs and has unique characteristics. In this context we note that there has been a recent discovery of a changing look phenomenon in an AGN 1ES 1927+654 (Trakhtenbrot et al 2019;Ricci et al 2020b;Laha et al 2022) the origin of which is still debated. However, the radio, optical, UV and Xray observations point towards an increase of accretion probably due to magnetic flux inversion, as the primary cause of this event (Scepi et al 2021;Laha et al 2022).…”
Section: Changing Look Nature Due To Change In Disk Profiles?mentioning
confidence: 86%